Isoniazid Induced Liver Injury; A Case Series and Review - Anusha, Ramatati; Chand, Sharad; Lal, Varun; Sushmitha, Devarapu Mary; Reddy, Dhypa Sahithi; Tejaswini, Siddha; Chitrahasini, Savanthi (Journal of Pharmacy Practice and Community Medicine)
Isoniazid is one of the most common drugs inducing liver injury, identifying and quantification of risk related to the drug is the prime to prevent and treat its occurrence. This case series tried to demonstrate the risk of drug (Isoniazid) by using the various causality assessment scales (RUCAM/CIOMS and Narnajo Algorithm). The cases taken were all males and taking the medication which on course develops the hepatotoxicity. It might be used as the literature for further study in addition similar studies are need to be carried out to understand the risk factor of drug induced liver injury.
Keywords: Isoniazid; Antitubercular therapy; Drug-induced liver injury; Hepatotoxicity